2002
DOI: 10.1002/ajpa.10073
|View full text |Cite
|
Sign up to set email alerts
|

Variation in soft‐tissue thicknesses on the human face and their relation to craniometric dimensions

Abstract: The average thickness of soft tissues on parts of the face is known, but its variation has not been related to cranial morphology. To investigate this relationship, measurements of facial soft-tissue depths and craniometric dimensions were taken on adult, white Australian cadavers (17 male and 23 female). Significant correlations between many soft-tissue depths and craniometric dimensions were found, suggesting a relationship between the amount of soft tissue present on the face and the size of the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
193
6
13

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(219 citation statements)
references
References 19 publications
7
193
6
13
Order By: Relevance
“…Some authors established high variability at lateral landmarks in the maxillary and mandibular regions [6], while the other noted large individual variation in the areas around lips and chin [24]. However, our results show that the most variable STTs established through CV are in the cheek and orbital region, and only gonion from the mandible variables appears in the most front positions.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…Some authors established high variability at lateral landmarks in the maxillary and mandibular regions [6], while the other noted large individual variation in the areas around lips and chin [24]. However, our results show that the most variable STTs established through CV are in the cheek and orbital region, and only gonion from the mandible variables appears in the most front positions.…”
Section: Discussioncontrasting
confidence: 63%
“…Besides, some of the authors have found greater STTs at the orbital region [20,21], forehead [20], chin [22,24] and skull vault [23]. Furthermore, El-Mehallawi and Soliman [13] revealed a notable sexual dimorphism in facial soft tissues with significantly greater STTs in females in most of the facial regions, including eye, cheek, lip, chin and jaw.…”
Section: Sex Differencesmentioning
confidence: 98%
See 3 more Smart Citations